Multidimensional competition of nematodes affects plastic traits in a beetle ecosystem - Renahan, Tess; Sommer, Ralf J. (Frontiers in Cell and Developmental Biology, 2022)
Resource competition has driven the evolution of novel polyphenisms in numerous organisms, enhancing fitness in constantly changing environmental conditions. In natural communities, the myriad interactions among diverse species are difficult to disentangle, but the multidimensional microscopic environment of a decaying insect teeming with bacteria and fighting nematodes provides pliable systems to investigate. Necromenic nematodes of the family Diplogastridae live on beetles worldwide, innocuously waiting for their hosts’ deaths to feast on the blooming bacteria. Often, more than one worm species either affiliates with the insect or joins the microbial meal; thus, competition over limited food ensues, and phenotypic plasticity provides perks for species capable of employing polyphenisms. The recently established system of cockchafer Gymnogaster bupthalma and its occasional co-infestation of Pristionchus mayeri and Acrostichus spp. has revealed that these worms will simultaneously utilize two polyphenisms to thrive in a competitive environment. While both genera maintain plastic capacities in mouth form (strictly bacterial-feeding and omnivorous predation) and developmental pathway (direct and arrested development, dauer), P. mayeri employs both when faced with competition from Acrostichus. Here, we took advantage of the malleable system and added a third competitor, model nematode Pristionchus pacificus. Intriguingly, with a third competitor, P. mayeri is quicker to exit dauer and devour available food, while Acrostichus hides in dauer, waiting for the two Pristionchus species to leave the immediate environment before resuming development. Thus, experimental manipulation of short-lived ecosystems can be used to study the roles of polyphenisms in organismal interactions and their potential significance for evolution.